Polimorfismos nos genes da via do hormônio do crescimento e efeitos nos índices produtivos em bovinos da raça Girolando - Queiroz, Luciana Benedetti de (2008)
The continuous investigation on gene polymorphisms may lead to the discovery of important associations with quantitative traits, explaining part of the existing variability. Considering the essential role of the somatotropic axis in the regulation of lactation, the purpose of this study was to associate polymorphisms of six genes: growth hormone releasing hormone (GHRH), growth hormone releasing hormone receptor (GHRHR), pituitary specific transcription factor 1 (Pit1), growth hormone (GH), insulin-like growth factor 1 (IGF1), insulin-like growth factor 1 receptor (IGF1R), with production traits of dairy cattle, such as: total milk production, average daily milk production and lactation period, analyzing the effects of gene interactions in bovine ⅝ Girolando. Genotyping of the 356 females was accomplished by the Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) technique. Statistical analyses were performed by using a mixed model and the averages grouped by genotype were compared by the Student t test. Results revealed a superiority of the heterozygote (GHRH/HaeIII) to total production (p < 0.01) and average daily milk production (p < 0.05). Favorable effects (p < 0.05) of the BB genotype compared to AA (Pit1/HinfI) and CC in relation to DD (GH/MspI) were also verified in the milk production. Additive effects of allele B (Pit1/HinfI) and C (GH/MspI) were observed in the milk production, generating an increase in the lactation of 116.2 kg and 68.51 kg of milk, respectively, for each incorporated allele. Through the analysis of gene interactions, a superiority (p < 0.05) of genotype BB (Pit1) in the presence of AA (IGF1) was demonstrated in total and average daily milk production. A shorter lactation period (p < 0.05) was still found in individuals with the genotypic combinations AA(Pit1)/BB(GHRHR), BB(Pit1)/AA(GHRHR), AB(IGF1)/AA(GHRH). The importance of gene polymorphisms in the GH pathway identified in this study suggests that these genes may become potential molecular markers to assist the selection of the Girolando breed as an auxiliary tool in genetic improvement programs.